HPLC-MS/MS determination and the postmortem distribution or postmortem redistribution of paraquat and its metabolites in four fatal intoxication cases. (April 2023) - Ma, Hongjuan; Hu, Meng; Zhang, Chao; Jia, Juan; Fu, Shanlin; Wei, Zhiwen; Yun, Keming
Abstract: HPLC-MS/MS analysis and postmortem distribution or postmortem redistribution of paraquat and its two metabolites in poisoning death cases were reported. Paraquat, monoquat, and paraquat monopyridone were extracted from the sample with acetonitrile or methanol, respectively, detected by ZORBAX HILIC Plus (4.6 × 100 mm, 3.5 μm) chromatographic column, with 0.1 % formic acid aqueous solution - 0.1 % formic acid acetonitrile solution (v/v) as mobile phase. Paraquat, monoquat, and paraquat monopyridone had a good linear relationship within the range of 10–1000, 1–400, and 1–1000 ng/mL (or g), the correlation coefficient (r) were all ≥ 0.9996. Their detection limits were lower than 1 ng/mL (or g). The detection accuracy was 91.25∼113.44 %. The intra-day and inter-day precision were 1.51–3.99 % and 1.92–4.93 %, respectively. This method was used to detect and analyze four rare paraquat poisoning cases. The distribution of paraquat, monoquat, and paraquat monopyridone is uneven, which is relatively high in the heart, blood, lung, and kidney. Heart blood/Peripheral blood ratio of paraquat, monoquat, paraquat monopyridone concentration in two poisoned cases were 1.4, 2.0, 1.5 and 1.9, 1.3, 1.2, which showed a location dependent postmortem redistribution. This is the first time that HPLC-MS/MS and the postmortem distribution or postmortem redistribution of paraquat metabolites in poisoned death cases have been reported. This research provides scientific basis for forensic identification of paraquat poisoning cases and extraction of biological specimen. Highlights: HPLC-MS/MS and PMR of PQ's metabolites in poisoned death cases were firstly reported.